The phenomenon of al-Asabiyyah in the Arab Peninsula: The historical study of its political and social role in early Islam / Ali B. R Elhrabi - Ali B. R, Elhrabi (2019)
The Phenomenon of al-Asabiyyah is considered the main distinguishing characteristic of the Arab tribes in the Arabian Peninsula before Islam. Its structure is based primarily on blood-links and genealogy, and to a lesser extent on alliance and neighborliness. This study aims to identify the political and social roles played by The Phenomenon of al-Asabiyyah in the early period of Islam. The social role appeared with the call to embrace Islam in Mecca, where the tribe of Quraish confronted this Islamic call with tribalism, but was not successful in putting a halt to it. After emigrating to Madinah, the Prophet (PBUH) began building his nation by fighting the negative aspect ofal-Asabiyyah, but he maintained and refined positive aspects of it. He founded a new bond stronger than the Tribal League. He founded the Association of Islamic Aqeedah or Faith, without touching the origin of the tribe as a social component. We will discuss how al-Asabiyyah took another face after the death of the Prophet (PBUH) in a mild form of alliances that started at the meeting of the roofed gallery (Saqeefah) between immigrants (Muhajireen) and supporters (Ansar). Later on it revealed its old face with the ‘wars of apostasy’ and the spread of Islamic conquests. It further became a regional al-Asabiyyah of political dimensions in the late Caliphate period and the beginning of the Umayyad state. In this study we will adopt the narrative analytic approach by presenting the historical positions and events related to this phenomenon, analytically, in order to reach the sought after conclusions, making use of the views of IbnKhuldun about al-Asabiyyah. The most important of the findings of this study is the assertion that The Phenomenon of al-Asabiyyah is not to be seen merely as an abhorrent behavior, but there are positive aspects to it, such as strengthening the relationship of the womb and knowledge of genealogy. Also it is found to have shifted from being an individual behavior to a collective program linked to alliances and loyalties, aiming to achieve political and economic objectives, especially in the late Caliphate. We strongly recommend taking a keen interest in studying The Phenomenon of al-Asabiyyah in order to use it to help address some issues of our contemporary crises in politics and governance. The phenomenon of clannishness is still very much present in our daily lives, but in other forms.